Germany's brake on European capital-market development - John Grahl; Photis Lysandrou (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
In February 2015, the European Commission published a Green Paper in which it put forward the goal to 'build a true single market for capital' for all European Union member states by 2019. The present paper argues that there is no realistic prospect of achieving this goal given that the Green Paper omits any reference to a formidable impediment blocking a European capital-market union: the German government's stance on debt. The inescapable fact is that this government's reluctance to increase the supply of its bonds is depriving the European capital market of one of the essential ingredients necessary to its enlargement on the one hand and to the efficiency of its operation on the other: the former because capital-market enlargement crucially depends on attracting institutional investors who must hold a substantial proportion of their bond portfolios in the form of safe government bonds; the latter because the efficient functioning of the capital markets crucially depends on the efficiency of the money markets where safe government bonds are by far the most important form of collateral.
Keywords: G15; F36; 330; Germany; debt brake; European capital-markets union